Transparansi Humas Sekolah dalam Menyampaikan Informasi Terkait Penahanan Ijazah oleh Sekolah - Siti Naila Safira; Tiara Tri Fitri; Ermita; Fifin Wildanah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This article presents a literature review on the issue of transparency in school public relations administration, especially in the management of diplomas in West Sumatra. Based on several references that have been reviewed, it was found that the manual method of diploma management and the lack of information system integration contributed to the low level of transparency. In addition, the role of public relations in conveying information to the public is considered suboptimal, which has implications for difficulties in monitoring and verifying data. This review aims to identify obstacles and provide recommendations for improvement to increase the accountability and efficiency of school public relations administration.